Prosedur Pendaftaran Objek Baru Pajak Bumi dan Bangunan Perdesaan dan Perkotaan Pada Badan Pendapatan Daerah Kabupaten Jember - Della Fitri Rahmadania (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Jember, 2025)
The registration of new objects of Rural and Urban Land and Building Tax is a very important initial step in the Land And Building Tax collection system. The implementation of the new object registration process makes people aware of the importance of registering their tax objects in addition to supporting local revenue. Registering PBB-P2 tax is useful for regulating property ownership so that owners can manage their land and buildings more efficiently. The objective to be achieved from the Real Work Practice is to find out the Procedure for Registering New Objects of Rural and Urban Land and Building Taxes at the Regional Revenue Agency of Jember Regency. This real work practice report uses data collection techniques through observation, interviews, and literature studies. The type of data used in the preparation of the report is qualitative data. Using two data sources, namely primary data and secondary data. The conclusion of this report is that the procedure for registering new urban rural land and building tax objects is the first step in the PBB-P2 tax collection system. Taxpayers can submit independently or be represented by an authorized person by providing a power of attorney to the Jember Regional Revenue Agency. By completing the supporting documents and filling in the blanks that have been determined by the regional revenue agency of Jember Regency. The final stage of the application is to submit a Regional Tax Assessment Letter of Less Pay to be paid by the taxpayer before the issuance of the SPPT.
Reuploud file repositori 8 Apr 2026_Firi_tata
Keywords: tax; local; land and building tax; new tax object; pbb-p2